Proyecto de factibilidad para la creación de una empresa dedicada a la prestación de servicios de catering a todas las instituciones y empresas de la ciudad de Loja - Morocho Armijos, Carlos Iván (2015)
This feasibility project aimed at the creation of a new company catering services in the city of Loja, is a new reality of today's market directed to provide food services for all workers in both public and private companies, is why it has considered business idea "a project on the feasibility of creating a company dedicated to providing catering services to all institutions and companies in the city of Loja." To meet this goal was necessary to use deductive, inductive, statistical and analytical methods and techniques of observation and survey which was applied to a sample of 397 public and private employees of the City of Loja to determine demand and 196 more restaurants in the city of Loja that offer lunches to determine the offer, may determine the existing unsatisfied demand was 482849 lunches. The project has an installed capacity of 48840 lunches and work for the first year with an installed capacity of 80% or 39072 lunches capacity, caterer services work in the city of Loja, in the streets Bolivar, Juan de Salinas and Jose Felix Valdivieso. Moreover, the Company will comply as limited liability and bear the name and address of: CHARLE'S CATERING CO. LTDA. "The investment required for the implementation of the project is $ 21,295.15, the cost of each lunch was estimated at $ 3.12, so the profit margin of 20% was established, which the sale price of each lunch about $ 3.75. The project is feasible and realizable as evidenced by the financial indicators such as NPV was worth 34244.94, the IRR was calculated at 63.12%. The initial investment will be recovered within 1 year 8 months and 24 days and the 5 cost benefit ratio indicates that you will get 0.20 cents for every dollar invested, while using sensitivity analysis was established that the project supports up 12.15 % increase in costs and 10.12% decrease in revenue. Once the work completed it was determined the most important conclusions were: The project is welcome as this is shown by the market study which determined that there is an unmet demand for 482849 services and according to the financial evaluation the project is profitable and rewarding. Finally among the important recommendations it is that the project implementation is recommended due to the results obtained from the evaluation criteria developed in this study, and periodically review the market and trends in order to prepare for the changes they can present to introduce new services to be better meet the needs of customers